Community Violence Exposure and Externalizing Problem Behavior Among Chinese High School Students: The Moderating Role of Parental Knowledge - Zhang, Yibo; Chen, Yuanyuan; Zhang, Wei (Frontiers in Psychology, 2021)
Adolescents’ community violence exposure(CVE) has been demonstrated with a range of behavioral and psychological problems, but the processes that explain these correlations are not clear. In our 2017 study, the mediating role of deviant peer affiliation in the relationship between CVE and externalizing problem behaviors has been confirmed. However, the moderating effect of parental factors is still unclear. Therefore, a new group (high school group) was adopted in this study to further explore the moderating effect of parental knowledge based on also confirming the mediating effect of deviant peer affiliation. Stratified-cluster sampling was used to recruit 1797 volunteers who have completed questionnaires on CVE, deviant peer affiliation, parental knowledge and externalizing problem behaviors. The results of structural equation modeling were: on the basis of our previous research, we further analyzed the mediating role of deviant peer affiliation, and the mediated association was moderated by parental knowledge; Specially, when the school climate is added as a covariate, the moderating effect of parental knowledge has changed, that is, the positive association between CVE and externalizing problem behaviors was much stronger for adolescents, who reported lower levels of parental knowledge than for those who reported higher levels of parental knowledge.The results support the assumptions of social learning theory and have implications for interventions of community violence.